2021
DOI: 10.1002/elps.202000302
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of a novel slowly mutating Y‐STRs set and evaluation of slowly mutating Y‐STRs plus Y‐SNPs typing strategy in forensic genetics and evolutionary research

Abstract: The Y‐chromosome short tandem repeats (Y‐STRs) loci with different mutation rates existing in the Y chromosome non‐recombination region (NRY) allow to be applied in human forensics, genealogical researches, historical investigations and evolutionary studies. Currently, there is a high demand for pedigree search to narrow the scope of crime investigations. However, the commonly used Y‐STRs kits generally contain Y‐STRs with high mutation rates that could cause individuals from the same pedigree to display diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…To satisfy such a requirement as much as possible, we developed this novel Y34plex panel that contained both slow to moderate mutation and rapid mutation markers. In details, Y-STR loci with slow-moderate mutations such as DYS593, DYS596, and DYS643 could be used for male pedigree searches [10,17,27]. Besides, the lineage resolution and total haplotype diversity were increased due to more markers incorporated, especially the addition of rapidly mutated markers [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To satisfy such a requirement as much as possible, we developed this novel Y34plex panel that contained both slow to moderate mutation and rapid mutation markers. In details, Y-STR loci with slow-moderate mutations such as DYS593, DYS596, and DYS643 could be used for male pedigree searches [10,17,27]. Besides, the lineage resolution and total haplotype diversity were increased due to more markers incorporated, especially the addition of rapidly mutated markers [28].…”
Section: Discussionmentioning
confidence: 99%
“…The Y34plex is designed to incorporate 31 single-copy loci, including DYS456, DYS627, DYS390, DYS570, DYS635, DYS448, DYS437, DYS533, DYS449, DYS481, DYS392, DYS391, DYS389I, DYS460, YGATAH4, DYS438, DYS389II, DYS19, DYS458, DYS439, DYS393, DYS576, DYS518, DYS557, DYS593, DYS444, DYS596, DYS643, DYS447, DYS549, and DYS645, and three multi-copy loci, including DYF387S1a/b, DYS527a/b, and DYS385a/b. All loci in Y34plex are chosen from the previously published literatures [15][16][17][18]. Then, markers are selected by the following criteria and procedures: (i) First, markers contained in widely used commercial kits are selected compulsively; (ii) the mutation rates of newly added markers should be less than 1.00E − 03, and the gene diversity values should be greater than 0.5 as far as possible; (iii) the nucleotide number of the core repeat motif cannot be less than three; (iv) the flank region of the selected loci should be suitable for primer design.…”
Section: General Information and Layout Of Y-str Locimentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study indicated that added RM Y-STRs would improve the efficiency of the system (Ballantyne et al, 2014) but mistakenly exclude male individuals from the same familial lineages, which could increase the difficulties of conducting paternal searching in the Y-STR database (Kayser, 2017). The SM Y-STRs are less likely to mutate among male relatives in the same pedigree, which makes this marker more suitable for forensic pedigree searches (Kayser, 2017;Liu et al, 2021). Therefore, we attempt to design a novel Y-STR panel with relatively low mutation rates of Y-STRs.…”
Section: Introductionmentioning
confidence: 99%